Analisis Penentuan Pusat Pertumbuhan Ekonomi dalam Pengembangan Wilayah di Kabupaten Labuhanbatu Utara, Provinsi Sumatera Utara - TAMPUBOLON, CONNY NATASYA; BUDIASA, I WAYAN; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Growth Pole Determination Analysis for Regional Development of North Labuhanbatu Regency, North Sumatra Province.  The gap between sectors and the unstable economic growth rate indicate that North Labuhanbatu Regency needs a regional development program. The research objective is to identify the classification of the economic sector in North Labuhanbatu Regency, determine the districts that are the growth poles, and interaction between areas known as growth poles with the surrounding areas. This study uses primary data with interview methods and secondary data with documentation methods. The indicators used are the Gross Regional Product (GRP) of North Labuhanbatu Regency and North Sumatra Province in 2015-2019, the population of each social and economic facility, the population of each sub-district, and the distance between sub-districts. The analysis was conducted using the typology classification method, the schalogram analysis and the centrality index, as well as the gravity analysis. The results show that the advanced and fast growing sector in North Labuhanbatu Regency is only the manufacturing industry sector. Districts that have the opportunity to become centers of economic growth in North Labuhanbatu Regency are Kualuh Hulu District and Kualuh Selatan District. Kualuh Hulu District has the closest interaction with other sub-district that is also a center of economic growth, namely Kualuh Selatan District.